Heparin-induced Thrombocytopenia Diagnosis: A Retrospective Study Comparing Heparin-induced Platelet Activation Test to 14C-serotonin Release Assay - Gonthier, Marie-Caroline; Gendron, Nicolas; Eloy, Philippine; Bourrienne, Marie-Charlotte; Alhenc-Gelas, Martine; Pouplard, Claire; Tardy, Bernard; Szymezak, Jean; Burdet, Charles; Gkalea, Vasiliki; Faille, Dorothée; Ajzenberg, Nadine (TH Open, 2021)
Laboratory confirmation of heparin-induced thrombocytopenia (HIT) is of crucial importance and remains challenging and relies on platelet functional assays highlighting the presence of heparin-dependent platelet-activating antibodies in patient serum or plasma. Platelet functional assays using washed platelets include the 14C-serotonin release assay (SRA), usually described as the gold standard, and the heparin-induced platelet activation assay (HIPA). Since its first comparison with SRA there has been no additional published study regarding HIPA diagnostic performances compared with SRA. Aim of our retrospective study was to compare the concordance between HIPA and SRA in HIT suspected-patients with positive anti-PF4/heparin antibodies between October 2010 and October 2015. Fifty-five HIT-suspected patients who beneficiated from both HIPA and SRA were included. Positive and negative percent agreements were 83.8% (95% CI 68.0–93.8%) and 66.7% (95% CI 41.0–86.7%), respectively. Overall percent agreement was 78.2% (95% CI 65.0–92.2%). Agreement was higher in patients who underwent cardiopulmonary bypass with extracorporeal circulation circuit for cardiac surgery. We also confirm that the use of a minimum of 2 platelet donors to establish positive HIT diagnosis and 4 platelet donors to exclude HIT diagnosis allows obtaining a good agreement with SRA. Although HIPA and SRA were performed with different platelet donors and in different laboratories, HIPA had a good positive agreement with SRA for HIT diagnosis, showing that HIPA is a useful functional assay that does not require radioactivity and could be developed worldwide to improve HIT diagnosis.
Keywords: heparin-induced thrombocytopenia; heparin induced platelet activation test; 14C-serotonin release assay; PF4/heparin antibodies; laboratory diagnosis